Stabilization via currency board - Jutta Maute (Universität Hohenheim, 2002)
The breakdown of the Argentine currency board in early 2002 produced a number of obituaries that often quite rashly declared the country's monetary constitution since 1991 the main responsible for its recent near-catastrophic economic collapse. Contrary to such rather one-sided negative ascriptions to the currency board system, the intention of this paper is to give a comprehensive and balanced description of the currency board model in theory, as well as to name its functioning conditions under today's economic and political conditions prevailing in developing and transforming countries. It will become clear that the success of a currency board in terms of lasting stabilization of an economy not only depends on its initial design (e.g. the choice of the anchor currency, of the exchange rate, the legal and institutional fixings) but also on an ongoing process of economic and institutional reform that extends from a general macroeconomic and especially public sector streamlining to banking sector reforms, product and labour market deregulation, and to a general realignment of the economy towards exportorientation and international competitiveness. The extent to which these reforms are tackled and completed decides over the degree to which the economy is able to absorb real shocks without incurring high economic and social adaptation costs, hence over the degree to which a country is able to benefit from the currency board's strengths without falling victim to its potentially severe weaknesses. Along with some basic reflections about the concept and motivation of modern currency boards, sections 1-3 give a brief overview over the historical background of the currency board idea as well as of its implementation. Section 4 focuses on the constitutional elements of a currency board, while section 5 provides the core of the discussion of pros and cons of currency boards, depicting the system's strengths and weaknesses as well as the conditions under which they materialize. Section 6 will discuss under which circumstances a currency board is a good choice for a country, and ask whether less strict stabilization policies might be able to deliver the hoped-for benefits less costly. Some problems related to the questions of duration and termination of currency boards are addressed in section 7. Finally, section 8 will give a brief exposition of the idea of dual currency boards as a theoretical extension of the currency board model which promises to eliminate one of the biggest immanent threats to a currency board.
urn:nbn:de:bsz:100-opus-4410
Keywords: E5; 330; Currency; Board